2003
DOI: 10.1677/erc.0.0100043
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding cassette transporters and drug resistance in breast cancer.

Abstract: Resistance to chemotherapy is a critical issue in the management of breast cancer patients. The nature of clinical drug resistance is likely to be multifactorial. However, in the last decade considerable attention has been dedicated to the role played by membrane transporter proteins belonging to the ATP binding cassette protein superfamily, and in particular by the MDR1 product P-glycoprotein (Pgp) and the multidrug resistance protein (MRP1). Heterogeneity of results is a common feature of studies evaluating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
182
1
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(196 citation statements)
references
References 182 publications
(210 reference statements)
6
182
1
7
Order By: Relevance
“…However, very limited data are available in the literature in this field and the precise mechanism of action, the relationship between multidrug resistance genes, and their clinical impact on the outcome of patients with breast cancer remain unclear, as published results have been discordant (Keith et al, 1990;Buser et al, 1997;Frassoldati et al, 1997;Silvestrini et al, 1997;Trock et al, 1997;Ferrero et al, 2000;Leonessa and Clarke, 2003). Few data are available concerning the impact of multidrug resistance genes on the clinical outcome of patients treated for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very limited data are available in the literature in this field and the precise mechanism of action, the relationship between multidrug resistance genes, and their clinical impact on the outcome of patients with breast cancer remain unclear, as published results have been discordant (Keith et al, 1990;Buser et al, 1997;Frassoldati et al, 1997;Silvestrini et al, 1997;Trock et al, 1997;Ferrero et al, 2000;Leonessa and Clarke, 2003). Few data are available concerning the impact of multidrug resistance genes on the clinical outcome of patients treated for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 27 patients, the risk of relapse in the 10 years following adjuvant chemotherapy was higher in patients whose primary tumours expressed higher levels of MRP1 mRNA (Ito et al, 1998). Heterogeneous results are a common feature of studies evaluating the expression and prognostic role of this gene, mainly due to both methodological and biological factors, and the prognostic impact of these two genes on DFS or OS remains to be established (Leonessa and Clarke, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was strongly suggested that expression of MRP1 gene is responsible for a negative response in early breast cancer and thus MRP1 gene expression levels can be used as marker for breast cancer (17). Leonessa et al have shown that early expression of MRP1 is directly correlated with a worse prognosis (18) while Trock et al demonstrated that MRP1 gene expression was in low levels before chemotherapy in breast cancer samples as compared to the samples after chemotherapy (19).…”
Section: Discussionmentioning
confidence: 99%
“…They are also expressed in cancer tissues and are important in determining resistance to specific chemotherapy agents such as the taxanes and topoisomerase inhibitors (13). Drug efflux is largely mediated by the ATP-binding cassette (ABC) transporters p-glycoprotein (P-gp) ABCB1 and breast cancer-related protein (BCRP) ABCG2.…”
Section: Introductionmentioning
confidence: 99%